The Role Of The Management Of The Nurul Hasanah Foundation In Shaping The Religious Character Of Orphans And Poor People In Bandar Khalipah Village, Percut Sei Tuan District - Nur Fadilah; Muhammad Basri (UNIVERSITAS PAKUAN, 2025)
This study aims to describe the programs implemented by the Nurul Hasanah Foundation and explore the role of administrators in shaping the religious character of orphans and dhuafa children in Bandar Khalipah Village, Percut Sei Tuan District. The method used is a descriptive qualitative approach with a field research type. Data collection was carried out through in-depth interviews, observation, and documentation. The results of the study indicate that the administrators of the Nurul Hasanah Foundation play an important role in shaping the religious character of children through various programs, such as Tauhid, Akhlak, and Fikih studies, learning the Qur'an, and congregational worship activities. In addition, the personal approach applied by the mentors also strengthens the internalization of religious values through close emotional relationships. Supporting factors in the formation of this religious character include a conducive environment, active involvement of administrators, and support from the surrounding community. This study concludes that the administrators of the Nurul Hasanah Foundation have a significant contribution in instilling religious values as moral and spiritual provisions for orphans and dhuafa children in living their lives in the future.